Electrocatalysis of Direct Methanol Fuel Cells 2009
DOI: 10.1002/9783527627707.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Alloys as Anode Catalysts for Direct Methanol Fuel Cells

Abstract: Pt À ðCH 3 OHÞ ads ! Pt À ðCOÞ ads þ 4H þ þ 4e À ð6:2ÞPlatinum is the most active metal for dissociative adsorption of methanol, but, as is well-known, at room or moderate temperatures it is readily poisoned by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 163 publications
(161 reference statements)
0
20
0
Order By: Relevance
“…In this direction, many research investigations have been focused on selection and synthesis of catalysts materials to enhance the methanol oxidation reaction (MOR) activity [19][20][21][22], Platinum based electrocatalysts are highly used for fuel cells, however their poor tolerance towards CO hampers its activity. Therefore, Ruthenium was additionally incorporated into platinum as a strategy to reduce CO poisoning of catalyst and to effectively promote conversion of CO to CO 2 in the DMFCs [23][24][25][26]. Still, poor performance, electrocatalytic activity and durability are considered as the major problem in Pt-Ru composites.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, many research investigations have been focused on selection and synthesis of catalysts materials to enhance the methanol oxidation reaction (MOR) activity [19][20][21][22], Platinum based electrocatalysts are highly used for fuel cells, however their poor tolerance towards CO hampers its activity. Therefore, Ruthenium was additionally incorporated into platinum as a strategy to reduce CO poisoning of catalyst and to effectively promote conversion of CO to CO 2 in the DMFCs [23][24][25][26]. Still, poor performance, electrocatalytic activity and durability are considered as the major problem in Pt-Ru composites.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of platinum poisoning by strongly adsorbed species coming from the dissociative adsorption of methanol has been addressed most commonly by the addition of cocatalysts, such as Ru, Mo, Sn, W, and Ni to Pt. Among them, the binary Pt–Ru system has been the most promising candidate and is the current state-of-the art MOR catalyst . However, direct methanol fuel cells using Pt–Ru anode catalysts operate at power densities approximately 10 times lower than that of a polymer electrolyte membrane fuel cell (PEMFC) fueled with hydrogen if the same noble metal loading is used.…”
Section: Screening Of Mor Electrocatalysts By Combinatorial Methodsmentioning
confidence: 99%
“…Considerable research has been done to improve the performance of Pt–Ru binary catalysts by the incorporation of a third or fourth metal. ,, The presence of a third/fourth component can significantly enhance the catalytic activity for methanol oxidation, supporting the oxidation of intermediate species and/or reducing their adsorption on Pt . Measurements of activity for methanol oxidation in half cells and/or in DMFCs showed that many ternary Pt–Ru-based catalysts better perform than that of the standard Pt–Ru catalyst .…”
Section: Screening Of Mor Electrocatalysts By Combinatorial Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the ligand or the electronic effect, the second metal modifies the electronic properties of the Pt by charge transfer processes and lowers the adsorption energy of alcohol oxidation intermediate species onto the Pt surface [5,7,8]. A broad variety of bimetallic catalysts, such as Pt-Ru, Pt-Sn, Pt-Ni, Pt-Co, Pt-W and Pt-Mo, were investigated to replace the monometallic Pt catalysts [9]. Among them, Pt-Ru and Pt-Sn catalysts showed a considerable improving of the electrocatalytic activity for the methanol The effect of the addition of nickel to platinum on the electrooxidation reaction of methanol can be mainly explained by the bifunctional mechanism and the electronic interaction between Ni and Pt.…”
Section: Introductionmentioning
confidence: 99%